2015
DOI: 10.5222/tmcd.2015.036
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli ve Klebsiella pneumoniae Suşlarında GSBL Üretiminin Saptanmasında VITEK- 2 Otomatize Sistemi ile Çift Disk Sinerji Testinin Karşılaştırılması

Abstract: Bu araştırma 12-16 Kasım 2014 tarihleri arasında Belek, Antalya'da düzenlenen XXXVI. Türk Mikrobiyoloji Kongresi'nde poster olarak sunulmuştur. Araştırma ÖZET Amaç: CLSI ve EUCAST'ın yenilenen dökümanlarında genişlemiş spektrumlu beta-laktamaz (GSBL) varlığının Anahtar kelimeler: Çift disk sinerji testi, GSBL, VITEK 2 SUMMARY Comparison of VITEK-2 Automated System and Double Disk Synergy Test for Detection of ESBL Production of Escherichia coli and Klebsiella pneumoniae Strains Objective: Although routine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For example, Yavuz et al [13] compared the ESBL production in Enterobacteriaceae strains with the DDS test and E-test methods and reported that there was no significant difference between the methods. Yurtman et al [14] and Akçam et al [15] did not detect a difference between the DDST test and E-test methods. Genç et al 16 in a study that compared VITEK-2 and DDS which investigated the presence of ESBL for 95 E. coli and 61 K. pneumoniae strains and reported that VITEK 2 sensitivity was 93.3%, specificity 81.8%, false-positivity ratio 18.1%, false-negativity ratio 6.6% and positivity ratio 86.4%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Yavuz et al [13] compared the ESBL production in Enterobacteriaceae strains with the DDS test and E-test methods and reported that there was no significant difference between the methods. Yurtman et al [14] and Akçam et al [15] did not detect a difference between the DDST test and E-test methods. Genç et al 16 in a study that compared VITEK-2 and DDS which investigated the presence of ESBL for 95 E. coli and 61 K. pneumoniae strains and reported that VITEK 2 sensitivity was 93.3%, specificity 81.8%, false-positivity ratio 18.1%, false-negativity ratio 6.6% and positivity ratio 86.4%.…”
Section: Discussionmentioning
confidence: 94%
“…[5,6] Various studies have been conducted in the literature on methods that detect ESBL production. [10][11][12][13][14][15][16][17][18][19][20][21][22] .9%, 96.0 was found when when molecular methods were taken as a reference. [10] Fincancı et al [11] was found screen test that based on zone diameter measurements is significantly sensitive compared to DDS and E-test methods for the ESBL detection sensitivity, similarly Oztürk et al [12] was found screen test that based on zone diameter measurements is concordant as E-test and more efficient than DDS.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the increase in antibiotic resistance rates in E. coli and K. pneumoniae strains, the causative agent of urinary tract infection, has been an important problem (4,5). The increase in antibiotic resistance rates makes it difficult to choose in empirical antibiotic treatment and causes the failure of treatment (1,2,5,11). In international guidelines, it has been recommended to determine local antibiotic resistance rates in the selection of empirical antibiotic treatment and not to use antibiotics with a resistance rate of more than 20% in empirical treatment (1,2,17).…”
Section: Discussionmentioning
confidence: 99%
“…For the test, bacterial suspension was prepared from colonies in fresh bacterial culture equal to 0.5 McFarland turbidity and transplanted into Mueller-Hinton Agar plaque. Three antibiotic discs [aztreonam (30 μg), ceftriaxone (30 μg), ceftazidime (30 μg)] were placed 20 mm away from the center of the amoxicillin-clavulanic acid (20/10 μg) disc and incubated at 37°C for 24 hours (11,12). Antibiotic susceptibilities of isolated E. coli and K. pneumonia strains were evaluated according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) criteria (13).…”
Section: Double-disc Synergy Testmentioning
confidence: 99%